Reichsrock : The International Web of White-Power and Neo-Nazi Hate Music - Dyck, Kirsten, 1983- (Book collections on Project MUSE., 2016)
Reichsrock shines a light on the international white-power music industry, the fandom it has spawned, and the virulently racist beliefs it perpetuates. Kirsten Dyck investigates how white-power bands and their fans have used the internet to spread their message worldwide, while closely examining distinctly local white-power scenes in the United States, England, Germany, Russia, Greece, and Latin America. Tracking the very real violence this music fandom has sparked, she sounds an urgent message about a global menace.